Analysis and Proposed Strategies to Improve Consumer Purchasing Decisions on Sean's Production Houses Through the Website - Zaluchu, Annette Zaneta; Barkah, Cecep Safa'atul; Chan, Arianis; Tresna, Pratami Wulan (Journal of Indonesia Marketing Association (IMA), 2023)
Sean's Production House is a company that specializes in branding & design, social media management, photography and digital marketing. GWI (Q3 2021) shows that 60.6% of people buy products or services online. This fact shows that the internet marketing and selling market is very large in Indonesia, so the market for Sean's Production House is very broad. However, after two years, only some consumers make purchasing decisions through the website. Companies need to spend a lot of money to create a website; the effort is also a lot. Due to these reasons, Sean's Production House closed its website in early 2022 because it was not making a profit. Sean's Production House requires the right business strategy to overcome this. After observations and interviews, the researcher realized that several factors made potential customers hesitate to purchase through the website. These factors relate to the gap between consumer expectations and the implementation of the website. Design thinking analysis is used to make a strategy to overcome it.